Dissolution Prediction of Fumaric Acid Crystal (Form A) in Ethanol using Molecular Dynamic Simulation - Nurul’ain Yusop, Siti; Anak Nili, Wirani; Anuar, Nornizar; Salwani Md Azmi, Nik; Fitri Othman, Muhammad; Abd Rahim, Syarifah (International Journal of Engineering and Technology, 2018)
Molecular dynamic simulation allows a better understanding on the dissolution behaviour of crystal in solvent. In this study, a dicarboxylic acid, fumaric acid crystal (Form A) is studied in ethanol which act as solvent. The morphology of fumaric acid (Form A) was successfully predicted, and the simulated lattice energy was compared with the experimental data and microphotograph of fumaric acid. The morphology was predicted using the CVFF forcefield and the lattice energy simulated was -32.8 kcal/mol, and 4.1% deviated from the experimental lattice energy. The elongated prismatic-like shape predicted morphology was in a good agreement with the microphotograph experimental fumaric acid. Ten morphological important facets were produced; (011), (020), (100), (110), (11-1) and their multiplicity. The mean square displacement (MSD) analysis through the diffusion coefficient showed that the diffusion of molecules from the crystal facets were from the following order: (11-1) > (100) > (110) > (011) > (020), which suggested the order of detachment of molecules from the respective facets. These findings were in agreement with the detachment observations carried out at 20ps of simulation, and also with the results of attachment energies, which corresponded to the growth rate of the facets and the molecular arrangement on the facets. Meanwhile, the radial distribution function on four facets showed that the molecular interactions due to van der Waals and Coulombic charges were detected in the following order: (11-1) > (110) > (011) and (100).